Impact of Trauma-Informed Practices on Social and Emotional Development in Early Childhood Classrooms (Journal of Asian Development Studies, 2026)
This study examined the impact of trauma-informed practices on the social and emotional development of young children in early childhood classrooms, particularly those with adverse childhood experiences (ACEs). Given the rising prevalence of ACEs and their negative effect on emotional regulation, social skills and classroom engagement, trauma-informed practices have emerged as a critical intervention within educational settings.A mixed-methods approach was used, combining quantitative data from the Social Emotional Assessment Measure (SEAM) and classroom behaviours observation with qualitative data from interviews with teachers. The study involved 15 early childhood educators and 120 children from three urban preschool classrooms selected based on having at least one year of trauma-informed practice implementation. The findings indicate marked improvements in children’s ability to manage emotions, interact positively with peers and participate actively in classroom activities over the school year.Teachers reported that using trauma-informed strategies, such as establishing structured classroom routines and fostering positive relationships, contributed to a supportive classroom environment and enhanced students’ performance. These results suggest that trauma-informed practices can play a key role in supporting the social and emotional development of children affected by adverse life experiences, highlighting the importance of integrating these approaches into early childhood educational training and practice to promote academic success and overall wellbeing of students.